Power Quality Control of Nonlinear Load using Custom Power Devices (International Journal of Engineering and Computer Science, 2016)
A Power quality problem is an occurrence manifested as a nonstandard voltage, current or frequency that results in a failure or a miss-operation of end user equipment’s. Utility distribution networks, sensitive industrial loads and critical commercial operations suffer from various types of outages and service interruptions which can cost significant financial losses. The present work is to identify the prominent concerns in this area and hence the measures that can enhance the quality of the power are recommended.